The influence of a maternal vegan diet on carnitine and vitamin B2 concentrations in human milk - Juncker, Hannah G.; van den Akker, Chris H. P.; Meerdink, Pauline L.; Korosi, Aniko; Vaz, Frédéric M.; van Goudoever, Johannes B.; van Keulen, Britt J. (Frontiers in Nutrition, 2023)
Background: The maternal diet greatly influences the nutritional composition of human milk. With the rise of vegan diets by lactating mothers, there are concerns about the nutritional adequacy of their milk. Two important nutrients, vitamin B2 and carnitine, are mostly ingested via animal products. Objective: We investigated the influence of a vegan diet on the vitamin B2 and carnitine concentrations in milk and serum of lactating women. Methods: In this case-control study, twenty-five lactating mothers following an exclusive vegan diet were comparted to 25 healthy lactating mothers with an omnivorous diet without use of supplement. High-performance liquid chromatography and liquid chromatography-tandem mass spectrometry were used to measure vitamin B2 and carnitine concentrations, respectively. A linear regression model was used to determine differences in human milk and serum concentrations between study groups. Results: Vitamin B2 concentrations in human milk and serum did not differ between study groups. While the human milk free carnitine (C0) and acetyl carnitine (C2) concentrations did not differ between study groups, serum carnitine concentrations were lower in participants following a vegan diet than in omnivorous women (p<0.0001). Conclusion: A maternal vegan diet did not affect human milk concentration of vitamin B2 and carnitine. Breastfed infants of mothers following an exclusive vegan diet therefore are likely not at increased risk of developing a vitamin B2 or carnitine deficiency.